Genetic mapping of a cone and rod dysfunction (Aland Island eye disease) to the proximal short arm of the human X chromosome. Issue 12 (December 1993) - Glass, I A; Good, P; Coleman, M P; Fullwood, P; Giles, M G; Lindsay, S; Nemeth, A H; Davies, K E; Willshaw, H A; Fielder, A
Abstract : A five generation family with an X linked ocular disorder has been investigated. The major clinical features were reduced visual acuity, nystagmus, and myopia. Although impaired night vision was not a symptom, using psychophysical and electrophysiological testing both rod and cone function were found to be abnormal in all affected males. No abnormality was detected in carrier females. Gene location studies showed X linked transmission of a gene that maps to proximal Xp11. The findings observed in this cohort are similar to those previously reported in both congenital stationary night blindness type 2 (CSNB2) and Aland Island eye disease (AIED). This study addresses whether CSNB2 and AIED are a single entity or whether the latter is a subset of the former.